EVALUASI ISI AWAL GAS DI TEMPAT DAN ANALISIS DECLINE CURVE PADA RESERVOIR YS - Yogie Seto S. W; Onnie Ridaliani; Lestari lestari (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
YS reservoir has data of gas initial in place (GIIP) with a volumetric method of 3,476 Bscf. Because of improvement of data, GIIP can be evaluated using material balance method. Then the production of wet gas will be forcasted until below economic limit. The PVT data that needs to be calculated in this study is the gas and water compressibility factor and the formation volume factor each year. In determining the type of drive mechanism, a plot of P / Z versus cumulative gas production is carried out, from the analysis, the type of drive mechanism is water drive, it is necessary to calculate the water influx, the method used is the Van Everdengen-Hurst method. After all the required parameters are available, the calculation of the initial gas in place will be calculated, the method used is the material balance method and the straight line material balance method. The results of the initial gas in place calculation using the material balance and straight line material balance methods are 3,430 Bscf and 3,428 Bscf. If the results of the material balance method and the straight line material balance method are compared with available GIIP volumetric method data, the percent difference is 1,32% and 1,37%. It can be said that GIIP result using the material balance method and the straight line material balance method is accurate because after being evaluated using volumetric method, it only has a small percentage difference. Then from the decline curve and Trial Error and X2 – Chisquare Test analysis, the decline curve is exponential with Di at 1,103 / month. After forecasting until production of wet gas is below the economic flow rate of 0,045 Mscf / d, it is known that the productive age is until 1st September 2021 with the values of EUR and RR respectively 2,309 and 0,014 Bscf. Using the results of GIIP using the material balance and straight line method, the current recovery factor are 67,34% and 67,37 %.